A Consensus Statement on the Surgical Treatment of Charcot-Marie-Tooth Disease. (July 2020) - Pfeffer, Glenn B.; Gonzalez, Tyler; Brodsky, James; Campbell, John; Coetzee, Chris; Conti, Stephen; Guyton, Greg; Herrmann, David N.; Hunt, Kenneth; Johnson, Jeffrey; McGarvey, William; Pinzur, Michael; et al.
Background: Charcot-Marie-Tooth (CMT) disease is a hereditary motor-sensory neuropathy that is often associated with a cavovarus foot deformity. Limited evidence exists for the orthopedic management of these patients. Our goal was to develop consensus guidelines based upon the clinical experiences and practices of an expert group of foot and ankle surgeons. Methods: Thirteen experienced, board-certified orthopedic foot and ankle surgeons and a neurologist specializing in CMT disease convened at a 1-day meeting. The group discussed clinical and surgical considerations based upon existing literature and individual experience. After extensive debate, conclusion statements were deemed "consensus" if 85% of the group were in agreement and "unanimous" if 100% were in support. Conclusions: The group defined consensus terminology, agreed upon standardized templates for history and physical examination, and recommended a comprehensive approach to surgery. Early in the course of the disease, an orthopedic foot and ankle surgeon should be part of the care team. This consensus statement by a team of experienced orthopedic foot and ankle surgeons provides a comprehensive approach to the management of CMT cavovarus deformity. Level of Evidence: Level V, expert opinion.